Morphological Character Study of Some Members of the Family Crassulaceae - Hanan Dabbub, (AlQalam Journal of Medical and Applied Sciences, 2025)
The vegetative morphology and leaf epidermal morphology of ten species in the family Crassulaceae were studied with the motive of providing information for the characterization and improvement of their classification. The present study was carried out to investigate the epidermal structure and types of stomata on the lower surfaces of the leaves in the species. The species, namely Aeonium decorum, Crassula capitella, Echeveria glauca, E. setosa, Graptopetalum paraguayense, Kalanchoe blossfeldiana, K. daigremontiana, K. fedtschenkoi, K. marmorata, and Sedum album. The species studied have some morphological diagnostic characters unifying, such as succulent habitats, perennial herbs, erect stems, simple leaves, leaf type, and succulent leaf structure. The great majority of petiole detection of the leaf was sessile, and the mostly margin leaf were mostly entire. Types of stomata on the lower surfaces of the leaves in all species showed anisocytic stomata, while the leaf epidermis cells had straight, undulate, or rounded anticlinal walls, as well as trichomes were only observed in Echeveria setosa. The stomata shape was mostly elliptic, and the epidermal cell shapes were found to be polygonal or irregular on abaxial surfaces in the studied taxa. Thus, the above-mentioned morphological character features are of great taxonomic significance and support the taxonomic description in this family.